Morphological diversity of culturable cyanobacteria from habitats in Segara Anakan, Central Java, Indonesia (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Fitri SGS, Sutarno, Sasongko H, Rosyadi H, Ratnasari M, Chairunisa S. . 2021. Morphological diversity of culturable cyanobacteria from habitats in Segara Anakan, Central Java, Indonesia. Biodiversitas 22: 5617-5626. Cyanobacteria are Gram-negative bacteria that can undertake oxygenic photosynthesis. This ancient group of microorganisms is ubiquitous, occurs in freshwater, marine, cold, hot, and terrestrial habitats. Can survive on a minimum requirement of light, carbon dioxide (CO2), and water, and able to fix the atmospheric N2 are among of their unique characteristics. These have collectively offered these bio-agents as the precious bio-resource for sustainable development. A variety of cyanobacterial strains promise further advances in biotechnology, including as an alternative source of energy. Before its final use, cyanobacteria undergo several necessary bioprocesses, including strain isolation and selection. This study aims to isolate and identify culturable-cyanobacteria from several habitats in Segara Anakan, Cilacap, Indonesia. The current study is an outset step to obtain potential and suitable agents for biofuel production. Morphological identification using light microscopy showed that cyanobacteria found in samples from different habitats varied. There are 39 cyanobacterial isolates obtained from freshwater, brackish water, and rhizosphere-mangrove soil habitats. Some cyanobacteria are unicellular (Order Chroococcales, Synechococcales, Pleurocapcales), the others are filamentous cyanobacteria (Order Oscillatoriales). These cyanobacteria grow well on BG-11 media. Numerous re-streakings on fresh medium and treatments of ampicillin and nystatin as antibiotic and antifungal, respectively, were carried out to obtain pure cultures. The classification of cultured cyanobacteria has been problematic and complicated. The polyphasic approach was applied to justify the taxonomic classification of the isolates. It is a combination of different methods based on modern molecular, cytomorphological, and ecological methods.
Keywords: Cyanobacteria, estuary, freshwater, mangrove, marine, Segara Anakan